Perceptions of paediatric surgeons on the selection & admission processes in Master of Paediatric Surgery : a qualitative study / Anand Sanmugam - Anand, Sanmugam (2021)
The selection and intake criteria for the paediatric training surgery training program (Master of Paediatric Surgery) has undergone changes. Changes were instituted to ensure a more robust selection system to ensure that the best candidates were selected into the program. However, there has not been any data to show that these changes have resulted in selection of candidates that could graduate on time and possess the attributes that predicted the development of competencies required. The aim of this study aim was to explore the perspectives of senior paediatric surgeons on the Master of Paediatric Surgery selection and intake process. The study used phenomenological qualitative research approaches and was based on the constructivist paradigm. In-depth structured interviews were conducted with senior paediatric surgeons in Malaysia with experience in the selection process. The viewpoint of these respondents with regards to the selection process before and after the introduction of the current selection process were sought. The relevance, strength and weaknesses of individual selection criteria were analysed. Opinions on areas of improvements in the current selection criteria were discussed as well. Most respondents agreed that a structured selection system, prior general surgery experience, involvement in scholarly activities and examinations were important in assessing applicants for selection. Less emphasis should be placed on years in service. Suggestions for improvement included improved applicant referee/supervisor engagement and the introduction of psychometric testing. In conclusion, despite a more structured, robust selection process of paediatric surgery trainees in Malaysia there is still room for improvement.